Intermuscular lipoma of the submandibular space - Patrícia Adachi; Shajadi P Kaba; Ana Maria P Soubhia; Elio H Shinohara (Wolters Kluwer Medknow Publications, 2011)
Deep lipomas, especially in the head and neck region, are uncommon. This report describes the case of a patient with a large intermuscular lipoma of the submandibular space, which had been present for 10 years and was diagnosed by computed tomography. The clinical, imaging, and histopathological features, as well as the management of the tumor, are described.